POLITICAL CRITIQUE OF AXEL HONNETH'S RECOGNITION OF JURGEN HABERMAS' DELIBERATIVE DEMOCRACY - sukri sukrie; Ishak Antok (Politea : Jurnal Politik Islam, 2023)
The purpose of this paper is to express Honneth's critique of Habermas' deliberative democracy. This research uses qualitative methods that are critically analytical in comparing the thoughts of Habermas and Honneth. The theory used is the sociology of knowledge from Karl Mannheim's. In the sociological theory of knowledge Mannheim says that man and his existence in the social environment can not be separated from his environment, a subjectivity that knows there is always interference from the social, political environment in which he lives. The results of this study reveal that the deliberative criticism of Democracy echoed by Habermas still leaves problems. The problem in deliberative democracies hints at rational communication, yet everyone does not have the same knowledge of rationality. For the educated person he has communication and knowledge rationally, but for the unlearned person does not have it, so they must represent his voice. In the Indonesian context, deliberative democracy is still wishful thinking. The public space referred to by Habermas has not yet gained a place in Indonesia, because the representation system that is the hallmark of representative democracy can be said to be pseudo-representation because there is no proportional bargaining position between constituents and their people's representatives. As Honneth's critique of Habermas the weakness of deliberative democracy, Honneth offers a form of intersubjective relation based on three areas of recognition namely love, self-confidence, self-respect, solidarity.